2004
DOI: 10.2166/wst.2004.0706
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(VI) by magnetite

Abstract: Magnetite nanoparticles were synthesized by sol-gel method. The highly crystalline nature of the magnetite structure with diameter of around 10 nm was characterized with transmission electron microscopy and X-ray diffractometry. The surface area was determined to be 198 m2/g. Batch experiments were carried out to determine the adsorption kinetics and mechanism of Cr(VI) by these magnetite nanoparticles. The Cr(VI) uptake was mainly governed by physico-chemical adsorption. The adsorption process was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
130
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(141 citation statements)
references
References 0 publications
10
130
0
1
Order By: Relevance
“…A similar behaviour was found for all tested concentrations, with equilibrium reached in 20 min in all of the cases. This time is comparable to the equilibrium time achieved by Hu et al (2004) and is lower than that obtained by Chowdhury et al (2012), who used magnetite-maghemite as the adsorbent. Subsequently, the effect of pH as well as of other parameters on the removal of Cr(VI) by the magnetite nanoparticles was studied with a contact time of 30 min to assure equilibrium.…”
Section: Effect Of Ph On the Cr(vi) Recoverysupporting
confidence: 45%
See 1 more Smart Citation
“…A similar behaviour was found for all tested concentrations, with equilibrium reached in 20 min in all of the cases. This time is comparable to the equilibrium time achieved by Hu et al (2004) and is lower than that obtained by Chowdhury et al (2012), who used magnetite-maghemite as the adsorbent. Subsequently, the effect of pH as well as of other parameters on the removal of Cr(VI) by the magnetite nanoparticles was studied with a contact time of 30 min to assure equilibrium.…”
Section: Effect Of Ph On the Cr(vi) Recoverysupporting
confidence: 45%
“…Several processes have been developed to eliminate the chromium present in industrial wastewater (Singh and Prasad 2015). The most commonly used methods to reduce the concentration of Cr(VI) in aqueous solutions are ion exchange, polymer resins, coagulation-flocculation, activated carbon adsorption and the reduction/chemical precipitation/sedimentation process (Boddu et al 2003;Hu et al 2004;Patterson et al 1997). Although the last method is probably the most commonly employed, it is very inefficient because a large amount of sludge is produced and the chromium cannot be recovered from the precipitate, making this strategy very expensive (Leyva Ramos et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although the biomedical applications of magnetite nanoparticles were extensively researched (9)(10)(11)(12), only limited research on its application in the environmental area were reported (13)(14)(15)(16)(17). While magnetite (13) and maghemite (14) nanoparticles were applied to the removal of Cr(VI), chitosan-bound Fe3O4 magnetic nanoparticles were prepared for the removal of Cu(II) ions (15). Ngomsik et al (16) gave a mini review on the application of magnetic nanoand microparticles in the removal of metals in wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…In acidic media, magnetite surface becomes more positive and so anionic Cr(VI) ions can easily be adsorbed on the magnetite surface by the effect of electrostatic attraction forces [18]. In addition, the magnetic sensitivity of magnetite also affects the removal of Cr(VI) [19]. Cr(VI) stock solution (500 mg/l) was prepared by dissolving 1.414 g K 2 Cr 2 O 7 with 1000 ml distilled water.…”
Section: Introductionmentioning
confidence: 99%